The control of screens and collective imagination. TV news and contemporary activism in Portugal - Müller, Naíde (2019)
The deep crisis of confidence affecting advanced industrial democracies that extends to the new and more recent democracies is creating a fertile ground for the growth of "populisms” that can affect significant activist historical achievements regarding basic human and civil rights. The debates about how social networks are contributing to this reality reinforces the need to strengthen the basic institutional and democratic functions of traditional media. In Portugal and in Europe television remains the most common medium used by citizens to access information, so it is important to present citizens other possibilities for public participation with the capacity to assert a set of social "counter-powers". The production of fictional realities increased by digital environments can be seriously detrimental to some audiences and postmodern PR professionals will necessarily have to adopt a critical attitude and vigilant of "meaningless communication" patterns. This article presents preliminary data on the representation of contemporary activist movements in the television news of the four generalist Portuguese free-to-air channels and approaches the possibilities for media professionals, as symbolmakers in hyperreality contexts, on counteracting the tendencies towards the standardization of beliefs in ways that can contribute to help activists, who defend democratic values, to reach the television screens.